2021
DOI: 10.1002/jssc.202001227
|View full text |Cite
|
Sign up to set email alerts
|

Rapid determination of 13 organophosphorus flame retardants in milk by using modified quick, easy, cheap, effective, rugged, and safe technique, solid‐phase extraction, and HPLC‐MS/MS

Abstract: Organophosphorus flame retardants are a class of widely used plasticizers and flame retardants. In this study, an analytical methodology for the simultaneous determination of 13 organophosphorus flame retardants in milk was developed by using high‐performance liquid chromatography‐tandem mass spectrometry in combination with a modified quick, easy, cheap, effective, rugged, and safe technique and solid‐phase extraction. The experimental parameters of the sample purification procedure and high‐performance liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Food samples were analyzed according to our previous study. , Briefly, a modified Quick, Easy, Cheap, Effective, Rugged, and Safe technique (QuEChERS) coupled to solid-phase extraction was used for sample pretreatment. Quantitative analysis was carried out by an Acquity HPLC (Waters, MA) coupled with an electrospray triple quadrupole mass spectrometry system (Micromass Xevo TQS, Waters, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Food samples were analyzed according to our previous study. , Briefly, a modified Quick, Easy, Cheap, Effective, Rugged, and Safe technique (QuEChERS) coupled to solid-phase extraction was used for sample pretreatment. Quantitative analysis was carried out by an Acquity HPLC (Waters, MA) coupled with an electrospray triple quadrupole mass spectrometry system (Micromass Xevo TQS, Waters, MA).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that a wide range of compounds with different polarities could be extracted by acetonitrile with a few lipophilic co-extracts such as lipid and pigments [30,31]. The extraction efficiency and stability of some acidic and base-sensitive pesticides could be improved by properly increasing the acidity of extraction solvent [32].…”
Section: Extraction Solventsmentioning
confidence: 99%
“…[18] Most existing methods for detecting TCEP involve gas chromatography and mass spectrometry (GC/MS), [19] as well as liquid chromatography and mass spectrometry (LC/MS). [20] Although these methods have relatively high reliability, they also have many disadvantages that cannot be ignored, such as long preprocessing time, slow analysis speed, high cost and so on, and therefore these have not been widely used.…”
mentioning
confidence: 99%